Multimorbidity in General Practice: Unmet Care Needs From a Patient Perspective - Rimmelzwaan, Lisanne M.; Bogerd, Mieke J. L.; Schumacher, Bregitta M. A.; Slottje, Pauline; Van Hout, Hein P. J.; Reinders, Marcel E. (Frontiers in Medicine, 2020)
Introduction: In the Netherlands, as in many other countries, current clinical guidelines are directed at single diseases. Patients with multiple chronic conditions may benefit from a more patient-tailored approach. Therefore, our objective is to explore the general practice care needs of patients with multimorbidity from a patient perspective. We also assessed their care experiences and the impact of chronic conditions on their daily functioning. Methods: We conducted a qualitative study, using semi-structured interviews complemented with self-report questionnaire assessments for triangulation, with consenting community dwelling patients with three or more chronic conditions. Participants were identified through purposeful sampling in three general practices. Two researchers independently coded and thematically analysed the audiotaped and anonymously transcribed interviews using the constant comparative method. The self-report questionnaire assessments were used to describe the patient characteristics and for triangulation of the data retrieved from the semi-structured interviews. Results: After 12 interviews, saturation was achieved. Overall, most participants were positive about their relationship with the general practitioner (GP) and practice nurse (PN) as well as the care they received in general practice. However, several unmet care need themes were observed. Firstly, lack of a holistic approach (by the GP and PN); in particular insufficient attention to the patient’s state of functioning, their limitations in daily life and their well-being. Secondly, they mentioned that personal continuity of care was imported to them and sometimes lacking. Thirdly, lack of patient-tailored explanations about diseases and treatments. Conclusion: From a community-dwelling multimorbid patient perspective, general practice care could benefit from improving personal continuity of care, attention to personal circumstances and daily functioning, and patient-tailored communication.